Impact of Comingled Heterospecific Assemblages on Developmentally Based Estimates of the Post-Mortem Interval—A Study with Lucilia sericata (Meigen), Phormia regina (Meigen) and Calliphora vicina Robineau-Desvoidy (Diptera: Calliphoridae) - Krystal R. Hans; Sherah L. Vanlaerhoven (Insects, 2021)
Estimates of the minimum post-mortem interval (mPMI) using the development rate of blow flies (Diptera: Calliphoridae) are common in modern forensic entomology casework. These estimates are based on single species developing in the absence of heterospecific interactions. Yet, in real-world situations, it is not uncommon to have 2 or more blow fly species developing on a body. Species interactions have the potential to change the acceptance of resources as suitable for oviposition, the timing of oviposition, growth rate, size and development time of immature stages, as well as impacting the survival of immature stages to reach adult. This study measured larval development and growth rate of the blow flies Lucilia sericata (Meigen, 1826), Phormia regina (Meigen, 1826) and Calliphora vicina Robineau-Desvoidy (Diptera: Calliphoridae) over five constant temperatures (15, 20, 25, 30, 35 °C), in the presence of conspecifics or two-species heterospecific assemblages. Temperature and species treatment interacted such that L. sericata larvae gained mass more rapidly when in the presence of P. regina at 20 and 30 °C, however only developed faster at first instar. At later stages, the presence of P. regina slowed development of L. sericata immatures. Development time of C. vicina immatures was not affected by the presence of P. regina, however larvae gained mass more slowly. Development time of P. regina immatures was faster in the presence of either L. sericata or C. vicina until third instar, at which point, the presence of L. sericata was neutral whereas C. vicina negatively impacted development time. Phormia regina larvae gained mass more rapidly in the presence of L. sericata at 20 °C but were negatively impacted at 25 °C by the presence of either L. sericata or C. vicina. The results of this study indicate that metrics such as development time or larval mass used for estimating mPMI with blow flies are impacted by the presence of comingled heterospecific blow fly assemblages. As the effects of heterospecific assemblages are not uniformly positive or negative between stages, temperatures or species combinations, more research into these effects is vital. Until then, caution should be used when estimating mPMI in cases with multiple blow fly species interacting on a body.